Changing aspirations, education, and migration: young people’s declining agroecological knowledge in rural Asia - Sugden, Fraser; Punch, S. (2016)
This chapter explores the interrelationships between economic change and environmental issues, by showing how aspiration, education, and migration are variously connected to a loss of agroecological knowledges for rural young people. It reviews a series of case studies from Vietnam, India, and China on the implications for rural youth of changed aspirations and ecological and economic stress. The economic and cultural pressures of globalization mean young people increasingly aspire for a life outside of agrarian- and natural resource-based livelihoods. A consequence of this change has been the migration of young people to urban centers and a drive for families to invest in education. Thishasfar reaching consequences for communities.Those who stay behind face an increased labor burden, and economic pressures can be aggravated when the promise of improved livelihoods outside is notrealized. The chapter also points to the negative implications of these changed aspirations on the intergenerational transfer of agroecological knowledge. Thus, in relation to issues of environment and development, the chapter considers why this complex set of relationships between aspiration, education, and migration is important in the context of children and young people’s lives.